Multimodal Approach of Isolated Pulmonary Vasculitis: A Single-Institution Experience - YILDIZELİ, BEDRETTİN; ALİBAZ ÖNER, FATMA; BEKİROĞLU, GÜLNAZ NURAL; ATAŞ, HALİL; DİRESKENELİ, RAFİ HANER (Elsevier Inc., 2021)
Background: Isolated pulmonary vasculitis (IPV) is a single-organ vasculitis of unknown etiology and may mimic chronic thromboembolic pulmonary hypertension (CTEPH). The aim of this study was to review our clinical experience with pulmonary endarterectomy in patients with CTEPH secondary to IPV. Methods: Data were collected prospectively for consecutive patients who underwent pulmonary endarterectomy and had a diagnosis of IPV at or after surgery. Results: We identified 9 patients (6 women; median age, 48 years [range, 23-55]) with IPV. The diagnosis was confirmed after histopathologic examination of all surgical materials. The mean duration of disease before surgery was 88.0 ± 70.2 months. Exercise-induced dyspnea was the presenting symptom in all patients. Pulmonary endarterectomy was bilateral in 6 patients and unilateral in 3. No deaths occurred; however 1 patient had pulmonary artery stenosis, and stent implantation was performed. All patients received immunosuppressive therapies after surgery. Mean pulmonary artery pressure decreased significantly from 30 mm Hg (range, 19-67) to 21 mm Hg (range, 15-49) after surgery (P < .05). Pulmonary vascular resistance also improved significantly from 270 dyn/s/cm–5 (range, 160-1600) to 153 dyn/s/cm–5 (range, 94-548; P < .05). After a median follow-up of 41 months, all but 1 patient had improved to the New York Heart Association functional class I. Conclusions: IPV can mimic CTEPH, and these patients can be diagnosed with pulmonary endarterectomy. Furthermore surgery has not only diagnostic but also therapeutic value for IPV when stenotic and/or thrombotic lesions are surgically accessible. A multidisciplinary experienced CTEPH team is critical for management of these unique patients. © 2021 The Society of Thoracic Surgeons